Comparativismo entre Alice e Emília: pontos e contrapontos das personagens de Lewis Carroll e Monteiro Lobato - Terres, Nathalia Ferreira (2018)
This research aims to compare the characters Alice and Emília, by studying the possible influence the author Lewis Carroll under Monteiro lobato. In this way, this study objects were the works Alice in Wonderland written by Lewis Carroll, Reinações de Narizinho, Memórias de Emília and A Chave do Tamanho by Monteiro Lobato. The methods utilized for the elaboration of the studies were researched in theories regarding children’s literature: Hunt (2010) and Lajolo e Zilberman (2010); in respect of fantastic literature, Todorov (2017); concerning comparative literature: Carvalhal (1992) and Nitrini (2010); about works’ production context: Irwin (2010) and Lajolo (2006). The results obtained through this comparative study show that there is intertextuality among the works studied and that Alice and Emília show similarities and disparities between them. Therefore, it is possible that Carroll’s literature has influenced Lobato.